An Information systems study on Philippine Public School Teachers Association mutual aid system - Abejo, Aurora; Constantino, Jocelyn; Crisostomo, Medel; Estiandan, Jo-Ann; Jimenez, Bobbitt; Joson, Rosalina (College of Engineering, 1987)
It has been said that learning should not be confined within the four corners of the classroom. For the aspiring Industrial Engineering student, this is but a painful reality. His theoretical knowledge, for it to grow, must be harnessed through application to real-world situations. For the IE54 course, the suitable venue for such an application would be a system where information plays a major role in the performance of that system's numerous activities. It is in this environment that things such as bubble diagrams, Warnier notation, decision trees, and other analysis tools for information systems find their "place in the sun". it is here where the student develops an appreciation for (or, if worse comes to worse, a disenchantment of) these techniques, so that, hopefully, when the man (not anymore a student) finally steps out to the world, he can stand erect with conviction, hold his head up high, and find the true meaning of his existence' as a full-fledged Industrial Engineer.